Efficiency Analysis of Rural Bank and Islamic Rural Bank in Central Java: Non Parametric Approach - Aufa Aufa; Evania Herindar; Mimma Maripatul Uula (FEBI UIN Sunan Kalijaga, 2022)
The purpose of this study is to examine the efficiency of the Islamic banking business in Indonesia, specially Rural Banks and Islamic Rural Banks. As a component of Indonesia's Islamic banking ecosystem, it is critical to understand the extent to which the two types of banks work optimally together to support the development of Islamic finance, particularly during the Covid-19 pandemic, and to realize public welfare, particularly through productive financing consistent with Sustainable Developmen Goals Objectives. In the periode of 2016 until 2020, this study examined a sample of 22 Rural Bank and 20 Islamic Rural Bank in central Java. The study was conducted using a non-parametric approach known as DEA (Data Envelopment Analysis). The intermediation strategy was used to determine the input and output variables in this study. Fixed assets, operational costs, and third-party money are included as input variables. Meanwhile, the output variable is made up of the quantity of finance granted and the amount of operating income earned. The findings of this study reveal that the efficiency of Rural Bank and Islamic Rural Bank in Central Java has a shifting tendency across the 2016–2020 timeframe, with the average bank experiencing a decline in efficiency during the COVID-19 pandemic. Additionally, when comparing the two types of banks in Central Java, Islamic Rural Bank has a greater efficiency level than Rural Bank. Additionally, this study assesses the possibility for improvement of inefficient programs using input and output data. The primary source of inefficiency is in the output variable, particularly in terms of customer financing. Additionally, this research makes recommendations to a variety of stakeholders, including practitioners, academics, and regulators